Model-making : materials and methods. - Neat, David, ....- (Wiltshire : Crowood, 2008)
Model-making: Materials and Methods focuses primarily on the wide variety of materials that can be employed to make models; those which have been favoured for a while and those which are relatively new.The book looks at how these materials behave and how to get the best out of them, then illustrates a range of relatively simple methods of building, shaping, modelling, surfacing and painting with them. Useful features of the book include:· The different uses of models in various disciplines· The sequence of making; planning and construction, creating surfaces, painting and finishing· Methods of casting, modelling and working with metals· Step-by-step accounts of the making of specially selected examples· Simple techniques without the need for expensive tools or workshop facilities· A 'Directory' of a full range of materials, together with an extensive list of suppliers